Multipurpose portable ramp / Muhammad Hafeez Ahmad Dawam ...[et al.] - Ahmad Dawam, Muhammad Hafeez; Rozali, Ali Imran; Nizam, Jas Mohd Shamir; Abd Rahim, Muhammad Nazmi Amzar; Mohd Khairil, Nur Irdina
From the problem statement above, the multipurpose ramp helps to ensure that the various users around us could perform their daily activities smoothly without facing any problem to move from different level of heights. The ramp mechanism is designed to make sure it is easy to bring at anytime and anywhere which it can be folded in order to save space and it is also lighter than any current ramps in the market. Besides, this multipurpose ramp helps to improve our user’s safety. This is where users do not have to lift up heavy things with their hands just like how they usually do while taking up the stairs which they could fall and injured themselves. Now, they can simply push the loads in an easier way all the way through the ramp. Since it is made from aluminium, users do not have to be worried about the weight limitations of this ramp because it is completely hard with strong bond particles. It will also not bend at all unless it has been used in a wrong method. Other than that, it could also help lessen the usage of human energy. The manual way needs the person to push and lift it by themselves. However, there will be no more because now they could just deploy the ramp without any helps from others.